(untitled) - Kirby, S. Woodburn (London, 1971)
The first is to give a sober, disinterested and as far possible accurate account of the events in the two decades before the war with Japan, events which made disaster inevitable. The second is to describe in general terms the strategy of the campaign, and to show how the galleant but ill-trained and ill-equipped garrison of Malaya tried to hope with Japan ese invasion...
Keywords: Singapore,Singapore; History,Lịch sử; 1942